1979
DOI: 10.1016/s0022-5347(17)56643-4
|View full text |Cite
|
Sign up to set email alerts
|

The Pigtail Ureteral Stent In The Cancer Patient

Abstract: Nephrostomy has been the standard procedure for urinary diversion when ureters are obstructed by cancer. However, recent reports have revealed significant problems related directly to the nephrostomy. The indwelling, internal ureteral stent eliminates many of these problems. We herein describe the course and survival of 20 patients in whom the pigtail ureteral stent was used to relieve ureteral obstruction caused by cancer. In these cases an over-all prolonged longevity, better quality of life and fewer compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 4 publications
0
27
0
2
Order By: Relevance
“…They are mainly indicated after any ureteral surgery and for managing ureteral obstruction due to intrinsic or extrinsic causes like stones, strictures, uretero-pelvic junction obstruction, retroperitoneal fibrosis, malignancies, and congenital anomalies (1)(2)(3)(4)(5). They are also placed after iatrogenic injuries to the ureter and before any complex abdominal procedure Clinical Urology doi: 10.1590/S1677-55382010000400005 for identification and protection of the ureters (6).…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly indicated after any ureteral surgery and for managing ureteral obstruction due to intrinsic or extrinsic causes like stones, strictures, uretero-pelvic junction obstruction, retroperitoneal fibrosis, malignancies, and congenital anomalies (1)(2)(3)(4)(5). They are also placed after iatrogenic injuries to the ureter and before any complex abdominal procedure Clinical Urology doi: 10.1590/S1677-55382010000400005 for identification and protection of the ureters (6).…”
Section: Introductionmentioning
confidence: 99%
“…ElFaqih et al found encrustation increased from 9.2% at less than 6 weeks' time to 47.5% at 6 to 12 weeks to 76.3% at more than 12 weeks of dwelling time. [7] …”
Section: Minimalmentioning
confidence: 99%
“…It allows good urinary drainage from kidney to bladder and is generally safe and well tolerated. They are mainly indicated after ureteral and renal surgery and are used for managing ureteral obstruction due to stones, strictures, ureteropelvic junction obstruction, and retroperitoneal fi brosis etc [1][2][3][4][5] . They are also used after iatrogenic injuries to ureter and before any complex abdominal procedure for identifi cation and protection of ureters 6 .…”
Section: Introductionmentioning
confidence: 99%